2019
DOI: 10.1002/jbmr.3708
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of MicroRNAs as Orthobiologics for Skeletal Fractures

Abstract: The repair of a fractured bone is critical to the well‐being of humans. Failure of the repair process to proceed normally can lead to complicated fractures, exemplified by either a delay in union or a complete nonunion. Both of these conditions lead to pain, the possibility of additional surgery, and impairment of life quality. Additionally, work productivity decreases, income is reduced, and treatment costs increase, resulting in financial hardship. Thus, developing effective treatments for these difficult fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 88 publications
(228 reference statements)
0
24
0
Order By: Relevance
“…MiRNAs are small non-coding endogenous RNA molecules (around 19–25 nucleotides in length), which regulate post-transcriptional gene expression [ 72 , 73 , 74 , 75 , 76 ]. Five miRNAs (miR-21-5p, miR-24-3p, miR-93-5p, miR-100-5p, and miR-125b-5p) were found also significantly upregulated in bone tissue from osteoporotic patients compared to controls [ 77 ].…”
Section: Catechinsmentioning
confidence: 99%
“…MiRNAs are small non-coding endogenous RNA molecules (around 19–25 nucleotides in length), which regulate post-transcriptional gene expression [ 72 , 73 , 74 , 75 , 76 ]. Five miRNAs (miR-21-5p, miR-24-3p, miR-93-5p, miR-100-5p, and miR-125b-5p) were found also significantly upregulated in bone tissue from osteoporotic patients compared to controls [ 77 ].…”
Section: Catechinsmentioning
confidence: 99%
“…A multitude of miRNAs are deregulated in osteoporosis in a cell-free, vesicle-free circulating form [83]. However, these are not readily comparable with the exosomal miRNA cargo; some are not consistently up- or downregulated in animal models of osteoporotic fractures in their free circulating form (miR-140-3p, miR-214), while others seem to promote both osteoclastogenesis and osteoblast differentiation in their exosomal form (miR-148a, miR-218) [84]. Nonetheless, both free and exosomal miR-29b-3p seem to enhance mouse fracture healing [84].…”
Section: Potential Clinical Implicationsmentioning
confidence: 99%
“…However, these are not readily comparable with the exosomal miRNA cargo; some are not consistently up- or downregulated in animal models of osteoporotic fractures in their free circulating form (miR-140-3p, miR-214), while others seem to promote both osteoclastogenesis and osteoblast differentiation in their exosomal form (miR-148a, miR-218) [84]. Nonetheless, both free and exosomal miR-29b-3p seem to enhance mouse fracture healing [84]. miRNA-21, which has been found upregulated in circulating exosomes of osteoporotic individuals, has an antiosteogenic impact, in that it inhibits SMAD7 protein with a subsequent downregulation of ALP , OCN , and RUNX2 [85].…”
Section: Potential Clinical Implicationsmentioning
confidence: 99%
“…Microribonucleic acids (microRNAs or miRs) are a type of single-stranded, non-coding and small-molecule RNAs approximately 18-25 nucleotides in length, which are involved in the occurrence and progression of various diseases ( 7 , 8 ). It has been reported that some miRs can participate in bone turnover, bone metabolism and bone development, thereby regulating the occurrence and progression of OP ( 9-11 ).…”
Section: Introductionmentioning
confidence: 99%